Global group work - Cohen, Carol S. (2012)
This article focuses on the Global Group Work Project’s action research study to explore and identify essential cross-national and cross-cultural elements of social group work practice, and to provide a model for international research and collaboration. It details study methods, process and outcome findings, analysis and recommendations.The key finding of the global themes of being together and doing together in social work groups, as well as the identify cation of local, indigenous practices contribute empirical knowledge about group work's international nature, with implications for teaching, research and practice.